2012
DOI: 10.1007/s10571-012-9804-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress Cardiomyopathy: A Syndrome of Catecholamine-Mediated Myocardial Stunning?

Abstract: During the past few years, a novel syndrome of heart failure and transient left ventricular systolic dysfunction precipitated by acute emotional or physical stress has been described. While patients with "stress cardiomyopathy"(SCM) typically present with signs and symptoms that resemble an acute coronary syndrome, it has become clear that this syndrome has unique clinical features that can readily be distinguished from acute infarction.In particular, in contrast to the irreversible myocardial injury seen with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 69 publications
(90 reference statements)
2
103
0
9
Order By: Relevance
“…LV myocardial dysfunction of TTC characterized by symmetric WMAs including the mid-ventricular segments of the anterior, inferior, and lateral walls (segment 7-12 based on the ASE guideline) over the apical segment (segment 13-17 based on the ASE guideline) should be considered peculiar to TTC and included in the differential diagnosis of TTC and acute coronary syndromes (31). These findings support the hypothesis of diffuse ventricular dysfunction secondary to myocardial stunning underlying the pathogenesis of TTC (32). Some earlier studies reported that advanced echocardiographic techniques, such as tissue Doppler imaging and speckle tracking imaging, could provide new insights into LV wall motion and systolic function assessment (33)(34)(35)(36).…”
Section: Wall Motion and Systolic Functionmentioning
confidence: 55%
“…LV myocardial dysfunction of TTC characterized by symmetric WMAs including the mid-ventricular segments of the anterior, inferior, and lateral walls (segment 7-12 based on the ASE guideline) over the apical segment (segment 13-17 based on the ASE guideline) should be considered peculiar to TTC and included in the differential diagnosis of TTC and acute coronary syndromes (31). These findings support the hypothesis of diffuse ventricular dysfunction secondary to myocardial stunning underlying the pathogenesis of TTC (32). Some earlier studies reported that advanced echocardiographic techniques, such as tissue Doppler imaging and speckle tracking imaging, could provide new insights into LV wall motion and systolic function assessment (33)(34)(35)(36).…”
Section: Wall Motion and Systolic Functionmentioning
confidence: 55%
“…Serum catecholamine concentration may be up to two to three times higher in patients with takotsubo cardiomyopathy compared to patients with myocardial infarction [17,20]. We postulate that as our patient was withdrawing from clonidine, he most likely had high serum catecholamine concentrations which precipitated the takotsubo cardiomyopathy variant.…”
Section: Reports Of Clonidine Withdrawalmentioning
confidence: 78%
“…The time that myocardium is at risk of being stunned is when it has a low reserve flow [4]. Acute emotional or physical stress can trigger a catecholamine-mediated myocardial stunning [5]. Extremely high plasma catecholamine levels and their metabolites elevation can cause stress cardiomyopathy resulting in stunned myocardium with transient ischemic change [6].…”
Section: Discussionmentioning
confidence: 99%